MENINGKATKAN KAPASITAS MASYARAKAT DALAM MENGATASI RISIKO BENCANA KEKERINGAN - maarif, syamsul (Badan Pengkajian dan Penerapan Teknologi, 2011)
Drought risk in Indonesia , particularly in Java Island will continuously increase. Global warming, environmental degradation, increased population, and poverty will more and more increase drought risk faced by the community. It is estimated that approximately 77% of the districts and cities in Java Island have experienced one to eight months of water deficit in one year. In 2025 the number of districts and cities experience water deficit will become 78.4% with a deficit from one month to twelve months or one full year. To reduce the risk posed by drought, community’spreparedness will need to be enhanced through the provision of water to deal with drought. Several rain harvesting techniques such as construction of water reservoirs, water tanks and absorption wells, as well as conservation of ground water, may be applied in high risks areas. Such rain harvesting techniques have indeed been implemented in many areas by traditional communities. Community’s capacity may be enhanced through continuous drought risk reduction programs that are based in the grassroots level and involve all relevant stakeholders. The role ofthe community becomes very crucial because in reality the people and local organizations constitute the keys in disaster risk reduction initiatives. The present initiatives involve community’s participation that is based on the following principles: based on the problems faced and the opportunities available in the community; using feasible solutions; encouraging partnerships with external parties; employing local knowledge and skills; focusing on the original conditions; and with clearly visible outputs.